2005
DOI: 10.1677/jme.1.01767
|View full text |Cite
|
Sign up to set email alerts
|

Suppressors of cytokine signaling proteins in human preterm placental tissues

Abstract: Decreased suppressors of cytokine signaling (SOCS) activity in human gestational tissues may play a part in the onset/progression of term labor. Since SOCS proteins negatively regulate cytokine-mediated inflammatory processes, we hypothesized that SOCS proteins are elevated in gestational tissues from spontaneous preterm deliveries with intrauterine infection. SOCS1, -2 and -3 mRNAs and proteins were detectable by RT-PCR and immunoblotting respectively, in preterm amnion, choriodecidua and placenta, irrespecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Hofbauer cells are also regarded as fetal macrophages capable of phagocytosis[109111] and production of cytokines [e.g., IL-1, IL-8, suppressor of cytokine signaling (SOCS) proteins][112114], chemokines [e.g. macrophage inhibitory protein (MIP)-1-beta][115] and phagocytosis-related enzymes [acid phosphatase (ACP) and glucose-6-phosphate dehydrogenase (G6PD)][111].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hofbauer cells are also regarded as fetal macrophages capable of phagocytosis[109111] and production of cytokines [e.g., IL-1, IL-8, suppressor of cytokine signaling (SOCS) proteins][112114], chemokines [e.g. macrophage inhibitory protein (MIP)-1-beta][115] and phagocytosis-related enzymes [acid phosphatase (ACP) and glucose-6-phosphate dehydrogenase (G6PD)][111].…”
Section: Discussionmentioning
confidence: 99%
“…The syncytiotrophoblast is a rich source of immunomodulatory molecules[118–120], and those with immunosuppressive properties [e.g. human chorionic gonadotropin, human placental lactogen, indoleamine 2,3-dioxygenase, CD95L/Fas ligand, pregnancy-specific beta-1 glycoproteins, SOCS proteins, TNF-related apoptosis-inducing ligand (TRAIL)][114,121–126] are proposed to attenuate maternal immune responses and, thus, maintain tolerance to the fetus. The evidence supporting that placental galectin-1 may also have an important role in immune tolerance includes the following: 1) Galectin-1 reduces host alloreactivity and ameliorates graft versus host disease in mice[81]; 2) it is capable of triggering the apoptosis of immature thymocytes[105] and activated T cells[75], biasing the immune responses to the Th2 type[63,127,128], and suppressing experimental T cell-mediated autoimmune diseases (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic crosses between mice heterozygous for deletion of SOCS3 and LIFRα (null mutants for each is lethal) revealed that the phenotype is due to dysregulation of signaling downstream of the LIFR and that the ligand responsible for this, LIF, is produced by embryonic tissues and acts in a paracrine fashion 28 , 95 . In human placenta SOCS1, SOCS2, and SOCS3 mRNA and protein are detectable in pre-term and term villous placenta and immunohistochemical analysis localized all three SOCS proteins to all decidual cells 97 , 98 . Interestingly, decreased SOCS3 expression has also been observed in the villous tissue of placentae obtained from women with preeclampsia 99 .…”
Section: Syncytialization Of Trophoblasts: Relevance Of Lif-stat Signmentioning
confidence: 99%
“…Proinflammatory cytokines and immune related chemokines stimulate prostaglandin production and uterine contraction through mechanisms that involve cycloxygenase-2 [34,40,41]. They act on cervical smooth muscles enhancing cervical ripening, activate matrix metalloproteinasess expression; and, increase protease production leading to extracellular matrix degradation, related cervical changes and premature rupture of membrane [34,40,41].…”
Section: Discussionmentioning
confidence: 99%